2016
DOI: 10.1016/j.bjane.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two different doses of morphine added to spinal bupivacaine for inguinal hernia repair

Abstract: For inguinal hernia repairs, the dose of 0.1mg of ITM provides comparable postoperative analgesia with a dose of 0.4mg, with significantly lower vomiting incidence when combined with low dose heavy bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…IT morphine can substantially reduce pain intensity for postoperative 12 h; however, there was no available data for advantageous outcomes of IT morphine on pain intensity at 24 h. 6 . A comparative study by Meco et al 2 . reported that 0.1 mg IT morphine added to intrathecal 7.5 mg bupivacaine in spinal anesthesia for inguinal hernia repair can be a good alternative than that of 0.4 mg IT morphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IT morphine can substantially reduce pain intensity for postoperative 12 h; however, there was no available data for advantageous outcomes of IT morphine on pain intensity at 24 h. 6 . A comparative study by Meco et al 2 . reported that 0.1 mg IT morphine added to intrathecal 7.5 mg bupivacaine in spinal anesthesia for inguinal hernia repair can be a good alternative than that of 0.4 mg IT morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal anesthesia is extensively used for both intraoperative anesthesia and postoperative analgesia management in IHR with the adverse effect concerns. The combination of intrathecal (IT) opioid and local anesthetic has been studied in these cases [2][3][4][5] . IT morphine can produce a long-lasting postoperative pain relief 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, ainda é controverso o período ideal para retorno a atividades profissionais após herniorrafia 7 . Em análises longitudinais, reparo bilateral de hérnia inguinal não apresenta morbidade maior do que correção unilateral, e retorno às atividades de vida diária tende a ser semelhante 14,15,18 .…”
Section: Discussionunclassified